2019
DOI: 10.1037/pst0000226
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy preferences of laypersons and mental health professionals: Whose therapy is it?

Abstract: What do patients prefer in their psychotherapy? Do laypersons and mental health professionals (as patients) want the same, or different, things? The authors systematically examined patients' psychotherapy preferences and quantitatively compared two samples of laypersons (N ϭ 228, 1,305) with one sample of mental health professionals (N ϭ 615) on the four dimensions of the Cooper-Norcross Inventory of Preferences: Therapist Directiveness Versus Client Directiveness, Emotional Intensity Versus Emotional Reserve,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 33 publications
(44 reference statements)
3
45
1
1
Order By: Relevance
“…The C-NIP assesses respondents' preferences for psychotherapist style (Cooper & Norcross, 2016). This tool, now translated into six languages, was primarily developed for routine assessment of clients' preferences in clinical practice but has also been used for research (Cooper et al, 2019). The inventory was constructed through principal component analysis of data from a convenience sample of US and UK laypeople and clinicians, responding as prospective clients (Cooper & Norcross, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The C-NIP assesses respondents' preferences for psychotherapist style (Cooper & Norcross, 2016). This tool, now translated into six languages, was primarily developed for routine assessment of clients' preferences in clinical practice but has also been used for research (Cooper et al, 2019). The inventory was constructed through principal component analysis of data from a convenience sample of US and UK laypeople and clinicians, responding as prospective clients (Cooper & Norcross, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Whereas most research on activity preferences has focused on preferences regarding the format of intervention (e.g., individual versus group therapy, Renjilian et al, 2001), our research concerned the styles or methods that clients would like their psychotherapists to use. Measures developed to support the investigation of such within-treatment activity preferences include the Psychotherapy Preferences and Experiences Questionnaire (Sandell et al, 2011), the Preference for College Counselling Inventory (Hatchett, 2015), and the Cooper-Norcross Inventory of Preferences (C-NIP) (Cooper & Norcross, 2016;Cooper et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The type of therapy an individual receives varies depending on many factors, including the type of psychological problem or disorder, therapist skill and availability, and personal preference. 16,17 Mental health problems such as depression and anxiety are commonly treated with psychotherapies that have a strong evidence base, such as cognitive-behavioural therapy; 18 are standardised and have high fidelity; and involve the use of psychotherapeutic strategies, such as pleasant event scheduling 19 or mindfulness techniques. 20 These strategies can be used to reduce the chance of disorder relapse 21 and improve coping with major life stressors.…”
Section: The Role Of Psychological Therapiesmentioning
confidence: 99%
“…Of these three, the working alliance has been most extensively subjected to empirical research and has been found to be a robust predictor of outcome (Horvath, Del Re, Flückiger, & Symonds, 2011). Other aspects of the psychotherapy relationship that received empirical support include empathy, congruence, and unconditional positive regard (Crits-Christoph, Gibbons, & N o n -c o m m e r c i a l u s e o n l y a therapist's relational style and a client's relational preferences may be an important factor influencing treatment outcomes (Cooper, Norcross, Raymond-Barker, & Hogan, 2019). Therefore, it is essential to understand the variety of relational styles used by therapists in practice.…”
Section: Introductionmentioning
confidence: 99%